МЕДИАКУЛЬТУРА И МЕДИАОБРАЗОВАНИЕ В ИНФОРМАЦИОННОМ ОБЩЕСТВЕ - Кунденко, Я. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Статья посвящена исследованию воздействия медиакультуры и медиаобразования на общественное сознание и индивидуальное мировоззрение человека информационного общества. Особое внимание уделено предпосылкам нового подхода к медиакультуре в сфере образования и науки, а также определению понятия «медиакультура» и «мифо-логическое мышление». Я.М. Кунденко ІНФОРМАЦІЙНЕ СУСПІЛЬСТВО – МЕДІАКУЛЬТУРА – МЕДІАОСВІТА Стаття присвячена дослідженню вплива медіакультури та медиаосвіти на суспільну свідомість та індивідуальний світогляд людини інформаційного суспільства. Особлива увага приділена передумовам нового підходу до медіакультури у сфері освіти та науки, а також визначенню поняття «медіакультура» та «міфо-логічне мислення». Ключові слова: медіакультура, медіаосвіта, інформаційне суспільство, «міфо-логічне мислення», засоби масової комунікації, мультімедійні технології, гіпертекст, інтерсуб’єктивність. J. Kundenkо MEDIACULTURE AND MEDIAEDUCATION IN THE INFORMATION SOCIETY The article is devoted to investigation of the influens of mediaculture and mediaeducation to the society concious and personal world-conception the human of the information society. Espessialy attantion is alloted to the reasons of the new mode to the mediaculture in the sphiere of education and science and also to definition of conception "mediaculture" and "mytho-logical minding". Key words: mediaculture, mediaeducation, information society, "mytho-logical minding", means ot mass communication, multymedia technology, hypertext, intersubjectivness.